2020
DOI: 10.3389/fpsyg.2020.00546
|View full text |Cite
|
Sign up to set email alerts
|

Do You Transfer Your Skills? From Sports to Health Management in Cancer Patients

Abstract: Skill transfer is a process where personal cognitive and behavioral abilities are applied to contexts that are different from the one in which they were originally learned. Literature demonstrates that skill transferability is possible: for example, people can apply skills learned in sports to other life-domains (such as school, work, or health management) with the aim to improve individual characteristics and reach personal goals. To do this, several factors, such as positive communication, adequate context, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 116 publications
1
12
0
Order By: Relevance
“…Zlomke and Hahn (2010) affirmed that the chronic efforts to suppress or avoid unsolicited internal emotions actually promoted the severity and frequency of negative emotional and cognitive experiences. On the contrary, reframing and acceptance of emotions were linked to adaptive psychological and behavioral functioning and (Sebri et al, 2020;Zlomke & Hahn, 2010). Finally, in reference to the association between worry and gender, Gould and Edelstein (2010) demonstrated that young women were more often worried compared to young men due to having less control over the external signs of emotion (Gould & Edelstein, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Zlomke and Hahn (2010) affirmed that the chronic efforts to suppress or avoid unsolicited internal emotions actually promoted the severity and frequency of negative emotional and cognitive experiences. On the contrary, reframing and acceptance of emotions were linked to adaptive psychological and behavioral functioning and (Sebri et al, 2020;Zlomke & Hahn, 2010). Finally, in reference to the association between worry and gender, Gould and Edelstein (2010) demonstrated that young women were more often worried compared to young men due to having less control over the external signs of emotion (Gould & Edelstein, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, literature shows the efficacy of novel and mixed approaches including psychotherapy-based interventions, physical exercise, and art/dance therapy to improve well-being in cancer patients and survivors (Björneklett et al, 2013 ), as well as cosmetic educational programs to promote self-esteem (Park et al, 2015 ). For example, mixed interventions featuring psychological support and physical activity (aerobic and resistance training especially) promote personal strength and quality of life (Fong et al, 2012 ; Benton et al, 2014 ) as well as improvements in cognitive abilities such as attention, working memory, and decision making (Sebri et al, 2019 , 2020a ). Regarding type of session, structured group, couple intervention, and formal one-to-one psychotherapy are the main formats of support within clinical settings (Fingeret et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, cancer patients develop notable introspection processes through the discovery of their own abilities and strengths and weaknesses, a knowledge particularly important to build a new sense of Self after the illness experience (Hodge and Lonsdale, 2011). Such abilities can be adapted and transferred in other life domains to increase personal skills, for example in cancer management (Pierce et al, 2018;Sebri et al, 2020). According to reviews and meta-analyses in the field, sport-based interventions generally have positive effects on breast cancer survivors' quality of life and health management (Craft et al, 2012;Bluethmann et al, 2015;Neil-Sztramko et al, 2019), although some specific physical activities appear less effective than others (e.g., TaiChi; Yan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%